Analysis of a SIS model to study the dynamics of disease spread when control measures are applied - Alpízar-Brenes, Geisel Yajaira (2016)
In this paper a discrete-time metapopulation SIS model is analyzed to determine the parameters that can be controlled and they represent the implementation of some control measure, in order to study their impact on the dynamics of the disease. When the parameters are defined, different scenarios are simulated to represent various real-life cases.